∫ 0 π ( 2 − cos x ) 2 d x
Evaluate the integral above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
but when i calculate this integral in calculator it comes out to be 3.1385........is it wrong....?
Log in to reply
you have your calculator set to degrees and not radians
Actually a great solution!
You should add a backslash before all functions including cos and tan in LaTex. See the difference \cos x " cos x ". The function name cos is not in italic which is for constants and variables and there is a space between cos and x. Now cos x " c o s x ", all are in italic and there is no space between cos and x. You don't need to enter text in LaTex. It is Brilliant.org's standard.
Nice solution. We can also solve it by integration by parts: ∫ 0 π d x d ( 2 − cos x − 1 ) × sin x 1 d x
I = ∫ 0 π ( 2 − cos x ) 2 d x l e t t = tan ( 2 x ) weierstrass substitution
cos x = 1 + t 2 1 − t 2 d x = 1 + t 2 2 d t I = ∫ 0 ∞ ( 2 − 1 + t 2 1 − t 2 ) 2 2 d t ⋅ 1 + t 2 2 d t = 2 ∫ 0 ∞ ( 2 − 1 + t 2 1 − t 2 ) 2 ( 1 + t 2 ) 2 1 + t 2 d t I = 2 ∫ 0 ∞ ( 2 + t 2 − 1 + t 2 ) 2 1 + t 2 d t = 2 ∫ 0 ∞ ( 1 + 3 t 2 ) 2 1 + t 2 d t l e t t = 3 tan ( x ) ⇒ d t = 3 sec 2 ( x ) d x I = 2 ∫ 0 2 π ( 1 + tan 2 ( x ) ) 2 ( 1 + 3 tan 2 ( x ) ) ⋅ 3 sec 2 ( x ) d x = 3 3 2 ∫ 0 2 π sec 2 ( x ) ( 3 + tan 2 ( x ) ) d x I = 3 3 2 ∫ 0 2 π ( 3 cos 2 ( x ) + sin 2 ( x ) ) d x = 3 3 2 ∫ 0 2 π ( 2 cos 2 ( x ) + 1 ) d x I = 3 3 2 ∫ 0 2 π ( 2 + cos ( 2 x ) ) d x = 3 3 2 ( 2 x + 2 sin ( 2 x ) ∣ 0 2 π ) = 3 3 2 π
Problem Loading...
Note Loading...
Set Loading...
Consider the following integral-
I = ∫ 0 π a − c o s x d x
It is pretty easy to evaluate I c o s x = 1 + t a n 2 2 x 1 − t a n 2 2 x
Simplifying,
I = ∫ 0 π ( a − 1 ) + ( a + 1 ) t a n 2 2 x s e c 2 2 x d x
So, take tan x/2 = t and obtain-
∫ 0 π a − c o s x d x = a 2 − 1 π
Differentiating both sides with respect to "a",
∫ 0 π ( a − c o s x ) 2 d x = ( a 2 − 1 ) 3 / 2 π a
Substitute a=2,
∫ 0 π ( 2 − c o s x ) 2 d x = 3 3 2 π